Pengaruh Co- branding dan FoMO terhadap Impulse Buying Gen Z pada Produk Kolaborasi Nabati dengan Girl Group Kpop Aespa di Surabaya - Alfiatus Zainiyah; Ayun Maduwinarti; Ute Cahirus M.Nasution (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
The rapid development of the bussines world requires companies to contiously innovate in order to remain competitive. Collaboration with Kpop artists have become a popular marketing strategy to attract consumers, as a demonstrated by PT Kaldu Sari Nabati Indonesia through its partnership with the girl group Aespa. This collaboration utilized co- branding strategies and leverages the Fear of Missing Out (FoMO) phenomenon, particularly prevalent among generation Z, potentially triggering impulse buying behavior. This study aims to examin the influence of Co- branding and FoMO on impulse buying behavior toward the Nabati with Aespa collaboration product in Surabaya. The research uses a quantitative approach with a questionnaire as the research instrument. The sample consist 100 generation Z repondents who have purchased the collaborative product, selected using purposive sampling. The result show that co- branding and FoMO have a significant effect, both partially and simultaneously, on impulse buying contributing 40,2% to the behavior. The reamaing influence is a attributed to other factor such as exclusive packing design and digital marketing. This study suggest that future researchers explore additional variabels and broaden the sample and population for deeper analysis.